Ion‐Intercalated Layers: Atomic Sn4+ Decorated into Vanadium Carbide MXene Interlayers for Superior Lithium Storage (Adv. Energy Mater. 4/2019). Issue 4 (24th January 2019) - Wang, Changda; Chen, Shuangming; Xie, Hui; Wei, Shiqiang; Wu, Chuanqiang; Song, Li
Abstract : In article number1802977 Shuangming Chen, Li Song and co‐workers utilize a synchrotron‐based operando XAS technique to in‐situ probe the dynamic Li‐ion charging/discharging process in Sn‐intercalated vanadium carbide MXene electrodes. The electrochemical activity and contribution of various atoms are clearly revealed, providing useful insight for better understanding of working mechanism of layered energy materials.